PENGARUH STRATEGI PROMOSI DIGITAL TERHADAP PENINGKATAN PENDAPATAN USAHA SANDO SAN GO - Tjakrakusuma, Vincentia Evita; Vidyarto Nugroho (Jurnal Bakti Masyarakat Indonesia, 2025)
Analysis of the Impact of Promotion Strategies on the Business Revenue of Sando San Go. This analysis aims to examine how promotion strategies affect the revenue of Sando San Go, with the goal of expanding its sales network and increasing thenumber of target customers in the culinary market. Promotionstrategy is one of the most important elements in marketing a product, as it can influence consumer decisions and have adirect impact on business revenue. In today’s fully digital era,innovation plays an essential role for business owners. Aside from improving unique flavors, it's also important to attract customer interest, which in turn influences the sales and income of Sando San Go. Promotion strategies such as using social media to create and share engaging content, offering discounts in exchange for following all of the business's social media accounts, and introducing new and unique flavors thatare not yet available in the market all these approaches can help boost product sales and business income. These digital promotional strategies were applied in this Student Creativity Program (PKM) by promoting eye-catching flyers through Instagram, WhatsApp, and other social media platforms, along with using engaging captions to attract potential customers. In addition, content such as appealing product photos was also created. The results of this PKM activity helped improve and develop business skills and provided valuable lessons, including how to handle the ups and downs of running a business. Sando San Go also became more widely known and popular across Indonesia. This analysis also indicates thateffective and creative promotional efforts, even with arelatively small budget and a simple production process, can be key factors in developing and growing micro, small, and medium enterprises (MSMEs) in the culinary market.   ABSTRAK Analisis pengaruh strategi promosi terhadap pendapatan usaha Sando San Go bertujuan untuk memperluas jaringan penjualan serta memperbanyak target pembeli Sando San Go di pasar kuliner. Strategi promosi adalah salah satu kunci penting dalam pemasaran produk usaha yang di jual serta dapat memengaruhi keputusan konsumen dan akan berdampak pada pendapatan usaha. Dalam kondisi dunia di era yang sudah serba digital ini menambah suatu keinovasian bagi para penjual, selain meningkatkan cita rasa yang unik juga meningkatkan ketertarikan para target untuk membeli produk usaha Sando San Go yang akan mempengaruhi pendapatan usaha. Strategi promosi seperti penggunaan media sosial sebagai wadah untuk membuat serta menyebarkan konten untuk menarik para target, pemberian diskon dengan cara mengikuti semua platform media sosial usaha, promosi dengan menghadirkan cita rasa yang baru dan unik serta belum dijual di kalangan pasar mana pun yang dapat meningkatkan pendapatan suatu produk usaha. Strategi promosi digital di atas tersebut digunakan sebagai metode pelaksanaan PKM ini dengan mempromosikan flyer yang dibuat semenarik mungkin melalui Instagram, WhatsApp dan media sosial lainnya beserta kata-kata yang menarik para target pembeli Sando San Go, dan pembuatan konten seperti foto produk yang eye catching. Hasil dari melakukan kegiatan PKM ini telah mengasah serta menambah skill dalam berbisnis kemudian dapat memberi banyak pelajaran seperti mengatasi suka dan duka dalam berjualan seperti apa dan juga Sando San Go telah dikenal banyak orang secara luas dan banyak digemari di Indonesia. Analisis ini juga mengindikasikan juga bahwa promosi yang efektif serta kreatif dengan modal yang relatif kecil dan dengan proses produk yang sederhana dapat menjadi faktor kunci dalam mengembangkan, meningkatkan usaha mikro, kecil, dan menengah (UMKM) di pasar kuliner.